Reaksi Pasar Modal Terhadap Kebijakan Pemerintah: Studi Kasus Pembentukan Danantara - Asa Tri Alvindo; Baihaqi Baihaqi; Adibah Syifa Khairunnisa (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study assesses the effect of the inauguration of the Danantara Indonesia Investment Management Agency on the abnormal returns of Badan Usaha Milik Negara (BUMN) under its management, and analyzes the difference in abnormal returns before and after the inauguration. Using a quantitative approach with the event study method, daily stock price data from nine BUMN on the IDX were analyzed over a seven-day observation period (D-3 to D+3). The Market Model was used to estimate abnormal returns, while the t-test and Wilcoxon signed-rank test were performed using SPSS 26. The results show significant abnormal returns on D-1, indicating that the information had been absorbed by the market prior to the formal announcement. No significant difference was found between the pre- and post-establishment periods, supporting the semi-strong form of the efficient market hypothesis.